Relationship of core power and endurance with performance in random intermittent dynamic type sports - Shaikh, A. I.; Nuhmani, S.; Kachanathu, S. J.; Muaidi, Q. I. (Asian Journal of Sports Medicine, 2019)
Objectives:To investigate the relationship of the core power and endurance with variables of athletic performance such as T test, medicine ball throw test, vertical jump test and 40 yard dash test in random intermittent dynamic type sports (RIDS).